REAKTUALISASI DAN KONTEKSTUALISASI PEMAHAMAN HUKUM ISLAM DI ERA INDUSTRI 4.0 - Akhmad Rudi Maswanto (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2019)
Islam indeed teaches truth and values ​​that are eternal and universal. However, the implementation and elaboration have the capacity to accommodate and accommodate the various interests of the people who continue to develop in accordance with the pace of civilization. Contextualization of Islamic teachings is actually not a new problem in the history of Islamic legal thought. The Companions of the Prophet especially Umar Ibn Al-Khaththab gave a concrete example of the need to understand the teachings of Islam in a contextual and essential way. Likewise, the difference of opinion among the mujtahid imams is a picture that the times, situations and conditions contributed a lot in determining various provisions of Islamic law. Even with the asbab al-nuzul theory, Nashik-mansukh and asbab al-wurud means al-Qur'an and hadith itself have considered a state of society in which the teachings will be enforced. Muslims (mujtahids) must not be confined by the literal textual provisions and understanding of the text. Contextual or even situational approach by prioritizing the essence and spirit of the soul of the Qur'an and hadith and based on the belief that the literal-textual provisions have flexibility and flexibility, then Islamic law will always be able to answer various problems that arise. In Islamic law there are 2 characteristics that have two key terms, namely: Sharia and Jurisprudence. Sharia consists of the revelations of Allah and the Sunnah of the Prophet Muhammad and fiqh is the understanding of the results of human understanding from the source of shari'ah. Shar'ah is